2014
DOI: 10.1049/mnl.2014.0382
|View full text |Cite
|
Sign up to set email alerts
|

Effect of current density on silicon surface in electrochemical etching

Abstract: A simple and reliable fabrication technique for producing nanoporous filters is presented. The nanoporous filter plays an important role in biomedical microelectromechanical systems applications, especially in filtering out waste and solute from inside human blood. Nanosized components in the biological fluid are filtered using silicon membranes that are controlled by nanosized pores. The technique explored was the electrochemical etching (ECE) process of silicon. This approach starts with thinning the bulk si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…This equation is also used by some researchers [31][32][33][34]. But other equations have been proposed in the process of liquidation in accordance with the method of surface oxidation of silicon, exchange hole and electrons that become a source of divalent silicon on the oxidation level [35].…”
Section: New Research On Silicon -Structure Properties Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…This equation is also used by some researchers [31][32][33][34]. But other equations have been proposed in the process of liquidation in accordance with the method of surface oxidation of silicon, exchange hole and electrons that become a source of divalent silicon on the oxidation level [35].…”
Section: New Research On Silicon -Structure Properties Technologymentioning
confidence: 99%
“…Ion dissolution process is dependent on the current density during the electrochemical etching process. The current density also affects the pore structure like spongy or columnar structure [33]. The current density is also among the parameters that can be manipulated to produce the perfect pore structure.…”
Section: New Research On Silicon -Structure Properties Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…For our application, the pore holes has to be columnar, with pore sizes of less than 50 nm. Our previous work has shown that pore sizes and uniformity are reproducible given the specific set of parameters [33,40,41].…”
Section: Ece Processmentioning
confidence: 99%
“…A high current density is needed to get columnar pore structure [22,40]. For this work, current density of 600 mA cm −2 was used with ethanol:HF at 1:1 ratio as the electrolyte.…”
Section: Pore Characterizationmentioning
confidence: 99%